2000
DOI: 10.1128/jcm.38.5.1998-2000.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Study of Campylobacter jejuni Genotypes in Humans with Domestically Acquired Infections and in Chicken Samples from the Helsinki Area

Abstract: Campylobacter jejuni isolates from stool samples of patients with domestically acquired sporadic infections and from chicken from retail shops were studied during seasonal peaks from June to September over a 3-year period from 1996 to 1998. A large number of pulsed-field gel electrophoresis (PFGE) genotypes (a combined SmaI-SacII pattern) were identified each year. Certain genotypes persisted for the whole study period, and predominant genotypes represented 28 to 52% of the strains during a restricted period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 10 publications
6
33
1
Order By: Relevance
“…These strains were noted several times both spatially and temporally, some identified in stores belonging to different supermarket chains. This finding is consistent with data obtained by Hanninen et al (2000) and Madden et al (1998) where certain recurrent patterns were noted over a 1 or 3-year period. Further study to determine the pathogenicity of these Campylobacter strains will shed light on the epidemiology of Campylobacter and underscore the public health significance of Campylobacter as a food-borne pathogen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These strains were noted several times both spatially and temporally, some identified in stores belonging to different supermarket chains. This finding is consistent with data obtained by Hanninen et al (2000) and Madden et al (1998) where certain recurrent patterns were noted over a 1 or 3-year period. Further study to determine the pathogenicity of these Campylobacter strains will shed light on the epidemiology of Campylobacter and underscore the public health significance of Campylobacter as a food-borne pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…Again, we do not have sufficient data to conclude that certain Campylobacter clones are host or niche specific. Studies looking at genotypes of Campylobacter from either animal or human sources did identify some strain types appearing to be associated only with humans, while other types are restricted to poultry (Koenraad et al 1995); however, most studies showed identical clones of Campylobacter could infect humans, poultry and cattle Hanninen et al 2000;Nielsen et al 2000;Fitzgerald et al 2001;Schouls et al 2003;Broman et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the human and poultry isolates of C.jejuni shared common PFGE patterns: SJ2KJ2, SJ6KJ6, SJ20KJ23 or SJ23KJ7. Because of the low number of human isolates, it is difficult to draw firm conclusions about the potential for transmission from broiler chickens to humans, as is the case in other countries (Hanninen et al 2000;. In Senegal, many enteritis sufferers do not seek medical attention and, even among those that do, only some will have a stool specimen cultured for enteric pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Several world-wide studies have indicated that poultry meats are commonly contaminated with Campylobacter. Reported rates of contamination include 36% in Denmark [14], 81.3% in Italy [15], 83.3% in the UK [16], 45% in Australia [17], 40% in Canada [18], 10-33% in Finland [19], and 70.7% in the US [20]. Ono and Yamamoto [2] reported a contamination rate of 45.8% among retail domestic poultry meat in Saitama, Japan, while here we found that 71.2% of retail poultry meat purchased in Akita, Japan, was positive for C. jejuni.…”
Section: Discussionmentioning
confidence: 99%